Remote treatment of developmental dyslexia: how ADHD comorbidity, clinical history and treatment repetition may affect its efficacy - Lorusso, Maria Luisa; Borasio, Francesca; Mistò, Paola; Salandi, Antonio; Travellini, Simona; Lotito, Mariangela; Molteni, Massimo (Frontiers in Public Health, 2024)
Tachidino is a web-based platform for remote treatment of reading and spelling disorders. In the present study, 136 children with developmental dyslexia received treatment via the Tachidino platform. The purpose of the study was to investigate the possible impact of different clinical conditions on the efficacy of treatment. The focus was on possible ADHD comorbidity-related effects on the outcomes of the Tachidino treatment, and the impact of previous treatments, such as speech and language therapy or the repetition of the same Tachidino program. The results showed that all children, irrespective of comorbidity, clinical history or treatment repetition, obtained significant benefits from the Tachidino remote treatment. Comparison with an untreated control group (waiting list) made it possible to exclude that improvement was due to test-retest learning effects. 1 Introduction In recent years, and mostly during the last months of the COVID-19 pandemic, telemedicine and remote treatments for Developmental Dyslexia have made it possible to keep rehabilitation programs active (1,2). Developmental Dyslexia (DD) is a heterogeneous learning disorder characterized by a severe and persistent impairment in the acquisition of reading and spelling skills that cannot be due to low intelligence, sensory or neurological damage, or poor educational opportunities (3,4). DD is currently best explained by multiple-deficits models (5-7) where phonological impairment may be symptomatic of a more basic deficit (8). It is therefore recommended that multiple-deficit models of dyslexia are taken into account in the remediation program choice (9).